Improvement of Private Capital Composition, its Analysis and Audit - D. Jonuzokov (International Journal on Economics, Finance and Sustainable Development, 2022)
This article examines how to improve the examination and audit of private capital, as well as its composition. Based on the findings of the research, suggestions were made to enhance the analysis, audit, and composition of private capital.